The Fund's Income Position for FY 2013-Actual Outcome. (Policy Papers; Policy Paper, 2013)
This paper reports the Fund's income position for FY 2013 following the closing of the Fund's accounts for the financial year and completion of the external audit. FY 2013 net income, including income from surcharges, amounted to SDR 2.0 billion, and was in line with the April estimate. In accordance with decisions taken in April 2013, a corresponding transfer of currencies has been made from the GRA to the investment account. The placement of the net income to the Fund's reserves has further strengthened the Fund's precautionary balances, which reached SDR 11.5 billion at the end of FY 2013.